The Profile Improvement of Vocational School Teachers’ Competencies - B. M. Triyono; N. Mohib; G. K. Kassymova; G. N. I. P. Pratama; D. Adinda; M. R. Arpentieva (Высшее образование в России, 2020)
This study is aimed to reveal the improvement in the competency of productive teachers of both state and private vocational high schools in Sleman Regency after participating in a self-development program in terms of psychological maturity and socio-cultural aspects. This study was carried out in two state vocational high schools SMKN 1 Sedayu and SMKN 1 Seyegan, and one private vocational high school SMK Muhammadiyah Pakem. It was a qualitative study in nature using interview and documentation as the means of collecting the data. Fifteen productive teachers of the three vocational high schools with expertise in Building Engineering Drawing (BED) were purposively selected to be the research subjects. The obtained data in the form of interview tapescripts, photos, and documents were triangulated to ensure data validity. The data were then analyzed systematically through three main stages including open coding, axial coding, and selective coding. The results show that through self-development, the BED productive teachers in state vocational high schools can improve their pedagogical and professional competencies. In addition, this program also develops their knowledge and skills in the areas of curriculum, expertise, technology, as well as teaching strategies and methods. Even so, in the case of BED productive teachers in private vocational high schools, this self-development program does not significantly improve their competencies.